Perceived importance of moderate‐to‐vigorous physical activity as a weight control strategy in behavioral weight loss - Marny M. Ehmann; Erica M. LaFata; Hannah C. McCausland; Francesca M. Knudsen; Meghan L. Butryn (Wiley, 2023)
Abstract Background Previous research has established the importance of moderate‐to‐vigorous physical activity (MVPA) for weight control. One area of unexplored investigation is the relationship between individuals' perceptions of the importance of MVPA for weight control and MVPA engagement. This study examined the associations between the perceived importance of MVPA and MVPA engagement, weight loss, barriers to PA, and exercise enjoyment in adults enrolled in a long‐term behavioral weight loss (BWL) intervention. Methods Adults (N = 301) with overweight/obesity (BMI = 27-45 kg/m2) completed an 18‐month BWL intervention, followed by a no‐intervention 18‐month follow‐up. At baseline, 6 months, 18 months (i.e., post‐treatment), and 36 months (i.e., follow‐up), participants ranked the importance of six strategies for weight control: keeping a food record, MVPA, light PA, self‐weighing, small portions, and low‐calorie diet. Observed MVPA (measured by accelerometer), percent weight loss, perceived barriers to PA, and exercise enjoyment were also measured at each assessment. Results Results showed that most participants perceived MVPA as a primary weight control strategy (first, second, or third most important) throughout the intervention, regardless of the weight control goal (weight loss vs. maintenance). Individuals who ranked MVPA as a primary strategy for weight control at concurrent time points, compared to those who did not, engaged in significantly more MVPA at post‐treatment, had greater weight loss at follow‐up, endorsed fewer barriers to PA at post‐treatment and follow‐up, and reported greater exercise enjoyment at baseline and post‐treatment. Conclusion Perceived importance of MVPA was related to subjective experiences of MVPA, MVPA adherence, and weight loss in a long‐term BWL intervention.